Strategi Startegi Internalisasi Nilai-nilai Agile Governance pada Pegawai Negeri Sipil di Lingkingan Pemerinah Provinsi riau: Agile Governance - Arfan, Surya (Komunitas Manajemen Kompetitif, 2024)
: This research aims to build a conceptual about how the internalization strategy of agile governance values to civil servants, with the aim of developing an internalization strategy of agile governance values in civil servants within the Riau Provincial Government. This study uses a qualitative method of methods by spreading questionnaires to related officials, as many as 225 respondents using a purposive sampling approach, data collection techniques using questionnaires with a scale It is the assessment of 10 strategies, namely strategies to meet the demands of public service, anticipating the threat of globalization, developing civil servant competencies, increasing creative and innovative to seize the potential of PAD, maximize the use of SPBE, open up broad opportunities for civil servants to follow competency development, utilize PNS Competency Development Institutions , in collaboration with universities and training institutions, utilizing high -leadership commitments, and utilizing the rapid development of information technology. This strategy will speed up civil servants to become world -class professionals. This research has never been done before.